Serum Total Bilirubin Level Is Associated With Hospital Mortality Rate in Adult Critically Ill Patients: A Retrospective Study - Yang, Zhou-Xin; Lv, Xiao-Ling; Yan, Jing (Frontiers in Medicine, 2021)
Background: Serum bilirubin level has been suggested to be associated with mortality for patients with severe sepsis. This study aimed to investigate the association of serum total bilirubin level with hospital mortality rate in adult critically ill patients. Method: Data were extracted from the Medical Information Mart for Intensive Care-III (MIMIC-III) database. Patients with measured serum total bilirubin levels that recorded within 24 h after admission were involved in this study. Association of serum total bilirubin level and hospital mortality rate was assessed using logistic regression analysis. Propensity score-matching (PSM) was used to minimize differences between different groups. Results: A total of 12,035 critically ill patients were herein involved. In patients with serum total bilirubin level ≥ 2 mg/dL, the hospital mortality rate was 31.9% compared with 17.0% for patients with serum total bilirubin level < 2 mg/dL (546/1714 vs. 1750/10321, P < 0.001). The results of multivariable logistic regression analysis showed that the odds ratio of mortality in patients with serum total bilirubin level ≥ 2 mg/dL was 1.654 [95% confidence interval (CI): 1.307, 2.093, P < 0.001]. After propensity score matching, in patients with serum total bilirubin level ≥ 2 mg/dL, the weighted hospital mortality rate was 32.2% compared with 24.8% for patients with serum total bilirubin level < 2 mg/dL, P = 0.001). Conclusions: Serum total bilirubin concentration was found to be independently associated with hospital mortality rate in adult critically ill patients.